Methodology for non-destructive identification of thickness of unilaterally accessible concrete elements by means of state-of-the-art acoustic techniques - Schabowicz, Krzysztof (Journal of Civil Engineering and Management, 2013)
The paper presents a methodology for comprehensive use of ultrasonic tomography and impact-echo – the state-of-the-art acoustic techniques – for non-destructive identification of the thickness of unilaterally accessible concrete elements. Since the techniques are not commonly used, they are little known. Therefore, a brief description of the techniques is given to facilitate the understanding of the subsequently presented methodology. The article gives a practical example of the use of the methodology, which demonstrates its suitability for non-destructive identification of the thickness of concrete elements, particularly those only accessible from one side. In the example, the concrete shell of a heat pipe, carrying tunnel located under a river was tested using the ultrasonic tomography and impact-echo techniques. The tests were carried out according to the proposed methodology. It should be noted that the test results yielded by the two methods were similar. In this way, the proposed methodology has been validated.